2010
DOI: 10.1253/circj.cj-09-0678
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Case Fatality Rates for Acute Myocardial Infarction in Weekday vs Weekend Admissions in South Korea

Abstract: Background: According to recent reports, reduced weekend staffing in hospitals may lead to a lower intensity of management of patients with acute conditions such as acute myocardial infarction (AMI). The present study evaluated differences in the case fatality rate of Korean patients admitted with AMI on weekdays vs those admitted on weekends. Methods and Results:The dataset was constructed from the Korea National Health Insurance Claims Database. The study population was 97,466 patients who were admitted to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Patients admitted on the weekend were less likely to undergo invasive cardiac procedures compared with patients admitted on weekdays, and a longer time from admission to procedures was also reported [10]. Similarly, Peberdy and colleagues [9] found that survival rates after in-hospital cardiac arrest are lower during the weekend.…”
Section: Commentmentioning
confidence: 96%
See 2 more Smart Citations
“…Patients admitted on the weekend were less likely to undergo invasive cardiac procedures compared with patients admitted on weekdays, and a longer time from admission to procedures was also reported [10]. Similarly, Peberdy and colleagues [9] found that survival rates after in-hospital cardiac arrest are lower during the weekend.…”
Section: Commentmentioning
confidence: 96%
“…Hospital resources may be different on weekdays compared with weekends, and the survival rates on weekends in cases of heart attack, stroke, and trauma are worse [6,7,9,10,[12][13][14]. The disparity in patient outcomes, the so-called weekend effect, has been well documented in a large number of previous studies of critical situations [6,7,9,10,13]. However, the weekend effect on ECPR has not been studied.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of off-hour admission for AMI on mortality has been controversial because previous studies have shown inconsistent results [1,[3][4][5][9][10][11][12][13][14][15]. Recently, a study using data from an administrative database in New Jersey reported that 30-day mortality for AMI was higher in patients admitted on weekends than on weekdays [10].…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not staf ing patterns dictate this interval, and what effect that may have on patient outcomes, is unclear. There have been a few reports that compare mortality rates among MI admitted on weekends compared to those admitted on weekdays, however, the indings have been inconsistent [6][7][8][9][10]. This has, in part, been due to difference in statistical adjustment, population size and proportion of PCI capable hospitals.…”
Section: Introductionmentioning
confidence: 99%